FUNGSI BHABINKAMTIBMAS DI POLSEK TAMANSARI POLRES BOGOR GUNA MENGANTISIPASI PENYEBARAN PAHAM RADIKAL DITENGAH MASYARAKAT DALAM RANGKA TERPELIHARANYA KAMTIBMAS - Indrayana, Galan Putra (Advances in Police Science Research Journal, 2019)
ABSTRACT This research is based on the high numbers of radicalism spread in the region of Tamansari Police Sector on Bogor Resort Police. The Radicalism engenders the disturbance in society. Indonesian National Police as the first line in anticipating the radicalism spread hasn’t done optimally. This research is solved using the elements and the principles of management, S.W.O.T analysis, and Community Police Officer Function as the bearer of Community Policing. This research is qualitative based research, using the interview, observation and document review as the technique for collecting data. This research is analyzed by data reduction, data presentation and drawing conclusions. Based on research, geographical and demographical of Bogor has not been accommodated by the police unit within structural and organizational strength. The lack in Element of management in Tamansari Sectoral Police affecting to the lack of implementation Community Police Officer in Tamansari Sectoral Police. There are factors which influence the assignment both internal and external which can be strength, weakness, opportunities, and threat for the implementation of Community Police Officer in Tamansari Sectoral Police to anticipate the spread of radicalism. The conclusion in this research is the importance of improving the Bogor Resort Police typology to Bogor City Resort Police, and cooperate with National Counter Terrorism Agency to be able to get assistance in technique, strategic and special operations in countermeasures radicalism. Keyword : Anticipating, Community Police Officer Function, Spread of Radicalism, Tamansari Sector Police Bogor Resort Police.